Analisis Pengaruh Pertumbuhan Ekonomi dan Kesempatan Kerja Terhadap Tingkat Kemiskinan di Kota Jayapura - Ema Dame Lasria Hutasoit; Agustina Ester Antoh (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2025)
This study aims to analyze the influence of economic growth and employment opportunities on the poverty rate in Jayapura City. Poverty remains a multidimensional challenge continuously faced by Jayapura City, although this region is known as the center of economic growth in Papua Province. Theoretically, economic growth indicated by an increase in Gross Regional Domestic Product and the expansion of employment opportunities is expected to reduce poverty levels; however, preliminary data shows that the relationship between these three variables is not always linear or consistent. The research method employed a quantitative approach using annual time series data from 2002 to 2024 sourced from the Central Bureau of Statistics of Jayapura City. The analysis was conducted using multiple linear regression with the poverty rate as the dependent variable, while Gross Regional Domestic Product at constant prices as an indicator of economic growth and the employment opportunity rate served as independent variables. Prior to regression, the data were tested for classical assumptions including normality, multicollinearity, heteroscedasticity, and autocorrelation to ensure model validity. Hypothesis testing was performed using the t-test to examine partial effects and the F-test to examine simultaneous effects. The results show that partially, both economic growth and employment opportunities have a negative and significant influence on the poverty rate in Jayapura City, meaning that any increase in these two variables will be followed by a decrease in the percentage of poor population. Simultaneously, both variables together also have a significant influence on the poverty rate and are able to explain almost all of the variation occurring in the poverty rate, thus confirming that economic growth and employment opportunities are the main determinants in the dynamics of poverty reduction in this region. Keywords: Poverty, GRDP, Employment Opportunities